Functions and functionaries of the Bangladesh Secrtariat - Huda, A.T.M. Shamsul; Mustafa a., Rehman
In pursuance of the popular inquisitiveness to know the activities inside the Bangladesh secretariat and their resulting impact on the intended beneficiaries, this study was undertaken to probe into the normal business of the functionaries therein at various functionaries therein at various hierarchical levels. A significant portion of the correspondences reveived by the secretariat is reported to be frivolous requiring no action at al. The action required cases remain either disposed or undisposed and of those which are disposed are being delayed as if delay has become the usual practice. It is, however, debatable whether delay is the cause or consequence of inefficiency. Moreover, effciency criteria rel
Keywords: Administrative; Efficiency; Bangladesh Secretariat; Efficiency, Administrative - Bangladesh